PENGARUH STRATEGI PEMASARAN DAN MINAT BELI KONSUMEN TERHADAP PENINGKATAN PENJUALAN PADA UMKM JERUK KALAMANSI ANGGREK PUTIH BENGKULU TENGAH (Pada Desa Harapan Makmur Kecamatan Pondok Kubang Bengkulu Tengah) - Gustian, David; Arini, Eti (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2023)
The purpose of this study is to find out how the influence of Marketing Strategy and Purchasing Power on Increasing Sales in UMKM Jeruk Kalamansi White Orchid Central Bengkulu The population used in this study is all employees working at PT Anugra Argon Medika Bengkulu Branch totaling 150 respondents. The sampling technique uses axial sampling based on creteria that has been determined to total 150 respondents. Observational data collection techniques, documentation and questionnaires. Based on the results of research that has been conducted on the influence of Marketing Strategy and Purchasing Power on Increasing Sales in MSMEs, Kalamansi Orange, White Orchid, Central Bengkulu. In Harapan Makmur Village, Pondok Kubang District, Central Bengkulu, it can be concluded as follows: Marketing Strategy has a significant effect on increasing sales in MSMEs Jeruk Kalamansi White Orchid Central Bengkulu. Purchasing Power to the Increase in Sales in MSMEs Kalamansi Orange, White Orchid, Central Bengkulu.Keywords: Marketing Strategy, Purchasing Power and Sales Increase